Quality of intrapartum care assessed by women participating in a midwifery model of continuity of care - Hildingsson, Ingegerd (Eur J Midwifery, 2021)
INTRODUCTION: Continuity models are rare in Sweden. The aim was to compare the intrapartum care experiences between women who had or not a known midwife attending their birth. METHODS: A cohort study was conducted in a rural area with long distance to a labor ward in Sweden. From August 2017 to June 2019, a continuity model with a known midwife was offered between 7 a.m. and 11 p.m. daily. Questions about intrapartum care were assessed in two aspects; the perceived reality and the subjective importance. RESULTS: A total of 226 women recruited in early pregnancy were followed up two months after giving birth. Women who had a known midwife providing labor care reported higher overall satisfaction and were more likely to value the subjective importance and the perceived reality significantly higher than women who received intrapartum care without a known midwife assisting. When analyzing the medical aspects of intrapartum care, the most important factors for not being satisfied were deficiencies in the partner’s involvement and insufficient pain relief. For the emotional aspects, deficiencies in participation in decision making was the most important aspect. CONCLUSIONS: Having a known midwife assisting at birth reduced discrepancies between women’s subjective importance and perceived reality of intrapartum care, especially regarding support and the involvement of the partner. A known midwife generated higher overall satisfaction with the medical and emotional aspects of intrapartum care. To improve satisfaction and the quality of intrapartum care, continuity midwifery models of care should be implemented.